EFEKTIVITAS KOMBINASI MICROWAVE DIATHERMY, STRENGTHENING DENGAN PENAMBAHAN FUNCTIONAL EXERCISE TERHADAP PERBAIKAN FUNGSIONAL KNEE PADA PENDERITA OSTEOARTHRITIS KNEE DI RSU. DR. TADJUDDIN CHALID MAKASSAR - Muhammad Awal; Sitti Fatimah Azzahra; Suharto Suharto; Sudaryanto Sudaryanto (Media Fisioterapi Politeknik Kesehatan Makassar, 2021)
Background: Osteoarthritis of the knee is a degenerative disease associated with joint cartilage damage. In general, people with osteoarthritis of the knee experience pain when supporting their weight, especially when walking and going up and down stairs.Methods: This study was a quasi-experimental study with a randomized pre test-post test control group design, aiming to determine the difference in effectiveness between the combination of Microwave Diathermy (MWD), Strengthening Exercise, Functional Exercise and the combination of Microwave Diathermy (MWD), Strengthening Exercise for functional improvement of the knee in patients with knee osteoarthritis, carried out at the RSU Physiotherapy Poly. Dr. Tadjuddin Chalid Makassar with a sample of 16 patients who fit the inclusion criteria, were randomly divided into 2 groups: the treatment group was given MWD, Strengthening and Functional exercise and the control group was given MWD and Strengthening.Results: Based on the analysis of the paired sample t test, the value of p = 0.000 (p <0.05) was obtained in the treatment and control groups, which means that the combination of MWD, Strengthening, Functional Exercise and the combination of MWD, Strengthening Exercise can provide significant functional improvement of the knee in knee osteoarthritis sufferers. The results of the independent sample t test obtained a value of p = 0.008 which means that there was a significant difference between the two sample groups in functional improvement of the knee.Conclusion: It can be concluded that the combination of Microwave Diathermy, Strengthening and Functional Exercise is more effective than Microwave Diathermy and Strengthening Exercise in improving functional knee in patients with knee osteoarthritis.Keywords: Microwave Diathermy, Strengthening Exercise, Functional Exercise, Knee Functional, Knee Osteoarthritis